Qualitative Assessment of Silage Prepared at Farmer’s Field in Tarn Taran District of Punjab - Brar, Navjot Singh; Kumar, Balwinder; Singh, Parminder; Kumar, Anil; Singh, Prahlad (Indian Journal of Animal Nutrition, 2017)
A comparative study for qualitative assessment of silage prepared from maize varieties alone (P-1844 and PAC-746) and combination of maize varieties (PAC-746 and 31Y45) with sugargraze at commercial dairy farms was carried out in Tarn Taran district of Punjab. The data were recorded with respect to maize hybrid grown, stage of harvesting (days after sowing), days taken to fill the pit and days of ensiling. After the opening of silo pit, the representative samples of silage were collected and quality analyses of these were carried out. The silages prepared from maize hybrid P-1844 (S1 and S2) harvested around 70 days after sowing (DAS) with ensiling period of 43 and 63 days, respectively recorded moisture content of 72.6 and 68.3%, DM content of 27.4 and 31.8% and CP content of 7.9 and 7.5%, respectively. The NDF content in silages S1 and S2 were 45.3 and 43.4% whereas ADF content values were 32.9 and 28.9%, respectively. The lowest (P<0.05) value of NH3-N (2%) was recorded for silage prepared from P-1844 while the highest (3.3% of total N) was recorded in silage from maize hybrid PAC-746. Different silages possessed pH in range of 3.8 to 4.0 and buffering capacity values between 3.9-4.2 meq./g. The aflatoxin contents for the silages were below 8 ppb. Therefore, it could be concluded that silage prepared from var. P-1844 (S1 and S2) recorded all